Severe Acute Respiratory Syndrome Coronavirus 2 Reinfection Associates With Unstable Housing and Occurs in the Presence of Antibodies. (10th November 2021) - Bean, David J; Monroe, Janet; Turcinovic, Jacquelyn; Moreau, Yvetane; Connor, John H; Sagar, Manish
Abstract: Background: The factors associated with severe acute respiratory coronavirus 2 (SARS-CoV-2) reinfection remain poorly defined. Methods: We identified patients with SARS-CoV-2 infection and at least 1 repeat reverse transcription polymerase chain reaction result a minimum of 90 days after the initial positive test and before 21 January 2021. Those with a repeat positive test were deemed to have reinfection (n = 75), and those with only negative tests were classified as convalescents (n = 1594). Demographics, coronavirus disease 2019 (COVID-19) severity, and treatment histories were obtained from the Boston Medical Center electronic medical record. Humoral responses were analyzed using SARS-CoV-2–specific enzyme-linked immunosorbent assays and pseudovirus neutralizations in a subset of reinfection (n = 16) and convalescent samples (n = 32). Univariate, multivariate, and time to event analyses were used to identify associations. Results: Individuals with reinfection had more frequent testing at shorter intervals compared with the convalescents. Unstable housing was associated with more than 2-fold greater chance of reinfection. Preexisting comorbidities and COVID-19 severity after the initial infection were not associated with reinfection. SARS-CoV-2 immunoglobulin G levels and pseudovirus neutralization were not different within the early weeks after primary infection and at a timepoint at least 90 days later in the 2 groups. In the convalescents, but not in those with reinfection, the late as compared with early humoral responses were significantly higher. Conclusions: Reinfection associates with unstable housing, which is likely a marker for virus exposure, and reinfection occurs in the presence of SARS-CoV-2 antibodies. Abstract : SARS-CoV-2 reinfection occurred at greater frequency among individuals with housing instability, and it did not associate with preexisting comorbidities or COVID-19 severity after first infection. Antibodies were detectable among the subset of individuals with documented reinfection examined in this study.